Post-partum Hemorrhage and Anemia as its Modifiable Risk Factor: A Literature Review - Anggraeni, Mekar Dwi; Setiyani, Rahmi; Setiawati, Nina (Jurusan Keperawatan FIKES UNSOED, 2019)
Maternal mortality is an indicator of a country’s health status. Postpartum hemorrhage is the main cause of maternal mortality. Understanding the postpartum hemorrhage risk factors useful to develop strategy in order to reduce maternal mortality. The aim of this study was to find modifiable postpartum hemorrhage's risk factors. This study used 6 steps which include formulating the research questions and objectives, searching the extant literature, screening for inclusion, assessing the quality of primary studies, extracting data, and analyzing data. The article was searched from Google Scholar and NCBI databases using bilingual keywords: